The organizational learning in Dominican Republic and Brazil - Manuel Alfonso Garzón Castrillon (Ingeniería y Desarrollo, 2009)
This paper comprises a research developed in organizational learning in the management of knowledge research area. The design required a theoretical model, and a test of 180 surveys applied to Executives from large, medium and small companies of Dominican Republic and 103 in Brazil. The general objective of the study is to characterize organizational learning and to determine how it influences the results of organizations. Finally observing the levels of significance for each one of the variables it is possible to conclude that all considered hypotheses H1, H2, H3, H4, were valid, finding that the capacity of organizational learning is directly influenced by the sources, the conditions and the culture of organizational learning, having as subjects the people, the equipment, the organizations and Inter-organizational learning.